Suppression of the Escherichia coli ssb-1 mutation by an allele of groEL. - Ruben, S M (1988)
A series of spontaneous suppressors to the temperature-sensitive phenotype of the single-stranded DNA-binding protein mutation ssb-1 were isolated. A genomic library of EcoRI fragments from one of these suppressor strains was prepared by using pBR325 as the cloning vector. A 10.0-kilobase class of inserts was identified as carrying the ssb-1 gene itself. A second class of 8.3-kilobase inserts was shown to contain the groE region by (i) restriction analysis, (ii) Southern hybridization of the 8.3-kilobase insert to groE+ DNA, and (iii) identification of the gene products by similar migration on polyacrylamide gels. Subcloning demonstrated that an intact mutant groEL gene was necessary for suppression and that plasmids carrying the 8.3-kilobase insert could suppress mutants carrying groES- but not groEL- genes for phage lambda growth. The suppressor, designated as groEL411, was specific for the ssb-1 allele. In ssb-1 groEL411 cells, DNA synthesis stopped after a shift to 42.5 degrees C but rapidly recovered within minutes. The data suggest a direct interaction between the single-stranded DNA-binding protein and GroEL proteins in DNA replication.